Individual and Organisational Differences Affecting Employees’ Satisfaction with Training Programs in Financial Services Triad - Al Madani, Asma; Alkooheji, Lamya; Al-Hattami, Abdulghani (Journal of Public Administration and Governance, 2023)
The financial sector plays a major role in the economy of the Kingdom of Bahrain. This study aimed at examining the relationship between individual and organisational factors in the financial services triad and the level of satisfaction with training programs. Using an online survey, 538 responses were collected from employees in the banking and finance, investment, and insurance sectors in Bahrain. The analysis showed that there was a significant correlation between employees’ satisfaction with training and their age, gender, who selected the program and the mode of delivery, while there was no correlation between their satisfaction with training and their speciality or length of work experience. The participants expressed interest in personalising the training plan to their own needs and goals; receiving more advanced training that is linked to personal and organisational strategic plans; receiving more interaction during the programs; and having problem-based cases and topics introduced into the training.